1994
DOI: 10.1111/j.1476-5381.1994.tb13100.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salmeterol on human nasal epithelial cell ciliary beating: inhibition of the ciliotoxin, pyocyanin

Abstract: Patients with airway infection by Pseudomonas aeruginosa have impaired mucociliary clearance. Pyocyanin is a phenazine pigment produced by P. aeruginosa which is present in the sputum of colonized patients, slows human ciliary beat frequency (CBF) in vitro and slows mucociliary transport in vivo in the guinea‐pig. We have investigated the effect of salmeterol, a long‐acting β2‐adrenoceptor agonist, on pyocyanin‐induced slowing of human CBF in vitro. Salmeterol (2 × 10−7 m) was found to reduce pyocycanin (20 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…The long-acting β 2 -agonist salmeterol raises the level of cAMP in epithelial cells [48], and partially inhibits the action of pyocyanin in vitro [49]. Therefore, salmeterol may benefit patients colonized by P. aeruginosa not only by its bronchodilating action but also by protecting cilia from the cAMPdependent effects of pyocyanin.…”
Section: Bacterial Interactions With Ciliamentioning
confidence: 99%
“…The long-acting β 2 -agonist salmeterol raises the level of cAMP in epithelial cells [48], and partially inhibits the action of pyocyanin in vitro [49]. Therefore, salmeterol may benefit patients colonized by P. aeruginosa not only by its bronchodilating action but also by protecting cilia from the cAMPdependent effects of pyocyanin.…”
Section: Bacterial Interactions With Ciliamentioning
confidence: 99%
“…Maintenance of ciliary beating of infected organ cultures in the presence of salmeterol could protect the epithelium against H. influenzae-induced damage by reducing the concentration of toxins in the microenvironment of the mucosal surface. However, the concentration of salmeterol (4×10 -7 M) used in these experiments has previously been shown not to affect ciliary beat frequency of epithelial cell monolayers [13] or nasal epithelial cells [17]. Salmeterol also increases intracellular cAMP [13].…”
Section: Discussionmentioning
confidence: 67%
“…We have previously shown that P. aeruginosa and its toxins pyocyanin and elastase damage human epithelial cells and that this damage is reduced by salmeterol [16]. Pyocyanin is a toxin whose effect is mediated via cAMP and we have previously shown that salmeterol attenuates pyocyanin-induced decreases in intracellular cAMP [17]. However, salmeterol also protected human nasal epithelial cells against P. aeruginosa elastase-induced damage, where the activity of the enzyme is not mediated via cAMP [16].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Antihistaminic drugs, beta blockers, general anesthetics, cocaine, etc., arrest the mucociliary clearance. Thus, NMC reduces the nasal bioavailability of drugs [21][22][23][24][25][26][27][28][29]. Various approaches for nasal delivery have been given in Table 3.…”
Section: Mucociliary Clearancementioning
confidence: 99%